PENGARUH SENAM TAI CHI TERHADAP KECEMASAN, STRES, DAN DEPRESI PADA DEWASA MUDA BER GAYA HIDUP SEDENTARI (SEDENTARY LIFE STYLE) - Sari, Anita Rapika; Rahmi, Upik; Rohaedi, Slamet; Wahdini, Ridha (Universitas Hamzanwadi, 2025)
This study was conducted against the backdrop of increasing sedentary behavior, which is negatively associated with mental health outcomes such as stress and anxiety, particularly among young adults facing academic pressures and psychological stressors. This research aimed to evaluate the effect of Tai Chi exercise on stress, anxiety, and depression levels among nursing students with a sedentary lifestyle. The study employed an experimental design with pretest-posttest assessments, involving 60 students randomly divided into intervention and control groups. The intervention group performed Tai Chi exercises for 40 minutes, three times a week, over 21 days, while the control group did not receive any intervention. Data were analyzed using independent t-tests. The results showed a significant decrease in anxiety and stress scores (p=0.001) following the intervention, whereas the effect on depression was not statistically significant (p=0.071). Overall, Tai Chi was effective in reducing anxiety and stress, although it did not significantly impact depression levels. In conclusion, Tai Chi can be used as a non-pharmacological method to improve mental health and reduce stress among students with a sedentary lifestyle.